The relationship between glycemia, insulin and oxidative stress in hereditary hypertriglyceridemic rat - Zourek, M; Kyselová, P; Mudra, J; Krcma, M; Jankovec, Z; Lacigová, S; Víšek, J; Rušavý, Z (Physiological research, 2008)
The aim of this study was to determine the effects of insulin infusion on oxidative stress induced by acute changes in glycemia in non-stressed hereditary hypertriglyceridemic rats (hHTG) and Wistar (control) rats. Rats were treated with glucose and either insulin or normal saline infusion for 3 hours followed by 90 min of hyperglycemic (12 mmol/l) and 90 min of euglycemic (6 mmol/l) clamp. Levels of total glutathione (GSH), oxidized glutathione (GSSG) and total antioxidant capacity (AOC) were determined to assess oxidative stress. In steady states of each clamp, glucose infusion rate (GIR) was calculated for evaluation of insulin sensitivity. GIR (mg.kg(-1).min(-1)) was significantly lower in hHTG in comparison with Wistar rats; 25.46 (23.41 - 28.45) vs. 36.30 (27.49 - 50.42) on glycemia 6 mmol/l and 57.18 (50.78 - 60.63) vs. 68.00 (63.61 - 85.92) on glycemia 12 mmol/l. GSH/GSSG ratios were significantly higher in hHTG rats at basal conditions. Further results showed that, unlike in Wistar rats, insulin infusion significantly increases GSH/GSSG ratios in hHTG rats: 10.02 (9.90 - 11.42) vs. 6.01 (5.83 - 6.43) on glycemia 6 mmol/l and 7.42 (7.15 - 7.89) vs. 6.16 (5.74 - 7.05) on glycemia 12 mmol/l. Insulin infusion thus positively influences GSH/GSSG ratio and that way reduces intracellular oxidative stress in insulin-resistant animals.
Keywords: Male; Rats, Wistar; reaktivní formy kyslíku; triglyceridy; Reactive Oxygen Species; Oxidative Stress; Animals; potkani Wistar; dusík močoviny v krvi; Glucose Clamp Technique; Metabolic Syndrome; antioxidancia; mužské pohlaví; glutathion; Hypertriglyceridemia; krysa rodu Rattus; glykemický clamp; oxidační stres; inzulin; Antioxidants; Rats; krevní glukóza; sérový albumin; Insulin; zvířata; Serum Albumin; Food Deprivation; potravinová deprivace; Glutathione; hypertriglyceridemie; metabolický syndrom; Triglycerides; Blood Glucose; Blood Urea Nitrogen